Influence of Organizational Cultural Leadership and Teamwork on Employee Performance With Organizational Commitment As an Intervening Variable: Pengaruh Kepemimpinan Budaya Organisasi dan Kerja Tim Terhadap Kinerja Karyawan dengan Komitmen Organisasi Sebagai Variabel Intervening - Purnomo, Bagus Cahyo; Astuti, Mudji (Universitas Muhammadiyah Sidoarjo, 2022)
This study aims to analyze the influence of leadership, organizational culture and teamwork on employee performance and analyze the influence of leadership, organizational culture and teamwork on organizational commitment and analyze the influence of leadership, organizational culture and teamwork on employee performance through organizational commitment as an intervening variable. This type of research is a research that uses quantitative methods. The location of this research, the researcher took the object of a campus organization, namely the Muhammadiyah University of Sidoarjo. The population used in this study was permanent employees of the Muhammadiyah University of Sidoarjo, which totaled 85 employees, using a sampling technique. Collecting data using a questionnaire. Analysis of the data using Path Analysis (Path Analysis). The results show that leadership, organizational culture and teamwork affect employee performance, then leadership, organizational culture and teamwork affect organizational commitment and leadership, organizational culture and teamwork affect employee performance through organizational commitment as an intervening variable. Leadership, Organizational Culture Teamwork Employee Performance Organizational Commitment.